Ketamine for Bipolar Depression: Biochemical, Psychotherapeutic, and Psychedelic Approaches - Bennett, Raquel; Yavorsky, Christian; Bravo, Gary (Frontiers in Psychiatry, 2022)
Bipolar disorder (type 1) is a serious and chronic psychiatric illness that can be difficult to treat. Many bipolar patients have refractory depressive episodes. Racemic ketamine, a glutamate modulator with prominent dissociate and psychedelic properties, has been demonstrated to have rapid acting antidepressant and anti-obsessional effects which may be useful for treating the symptoms of bipolar depression. Most of the existing research literature on unipolar and bipolar depression has looked at racemic ketamine in the sub-psychedelic dose range given by infusion as a stand-alone treatment (without concurrent psychotherapy). This article expands on the existing research by articulating three different paradigms for ketamine treatment: biochemical, psychotherapeutic, and psychedelic. The authors use composite clinical vignettes to illustrate different ways of working with ketamine to treat bipolar depression, and discuss a variety of clinical considerations for using ketamine with this population, including route, dose, frequency, chemical mitigators, and adverse events. Note that the conceptual paradigms could be applied to any ketamine treatment, with broad applicability beyond bipolar treatment.